Development of Electronic Encyclopedia Chemistry Laboratory (e-EncyLab) by Using 3D Pageflip Professional to Improve Chemistry Laboratory Literacy Level - Linawati Linawati; Asmadi M. Noer; Lenny Anwar S; Betty Holiwarni (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
This research aims to determine the effectiveness of chemistry laboratory literacy levels by developing an e-EncyLab using 3D Pageflip Professional. This study employs a quantitative research methodology. The participants were 10th-grade students. Data was collected using a set of 12 essay questions designed to assess chemistry laboratory literacy, available in the e-EncyLab. Increasing laboratory literacy level abilities can be determined using the N-gain test. The results of this research showed an increase in N-Gain of 0.68 in the medium category. The effect of using e-EncyLab in increasing chemistry laboratory literacy is shown by the results of the paired sample test, which shows sig 0.000 < sig 0.05, which means there is a significant difference in the level of chemistry laboratory literacy of students in the control class and the experimental class that uses e-EncyLab. The use of e-EncyLab is effective in increasing students' chemistry laboratory literacy.